Debunking the Concept of Liberalism A Critical Review: Membantah Konsep Liberalisme Sebuah Tinjauan Kritis - Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2024)
This study critically examines the basic tenets of liberalism and their implications for the discourse between Islam and the West. With reference to texts from thinkers such as John Locke and John Stuart Mill, it challenges the rationality and coherence of liberal ideology, particularly regarding equality, freedom and hedonistic morality. Islamic perspectives on these issues are considered, highlighting differences in epistemological foundations. The research underscores the need for nuanced dialogue and critical inquiry, emphasizing the importance of epistemological diversity in addressing the challenges of contemporary society. Highlights : Critiquing liberal ideology: equality, freedom, morality coherence challenged. Contrasting Islamic epistemological foundations with liberalism's rationality. Emphasizing nuanced dialogue and diverse epistemology for contemporary challenges. Keywords: Liberalism, Islam, Dialogue, Epistemology, Diversity